Production of Secretory Leucocyte Protease Inhibitor (SLPI) in Human Pancreatic β-Cells - Max Nyström; Magnus Bergenfeldt; Irena Ljungcrantz; Èsa Lindeheim; Kjell Ohlsson (Mediators of Inflammation)
Secretory leucocyte protease inhibitor (SLPI) is a potent inhibitor of granulocyte elastase and cathepsin G, and also an inhibitor of pancreatic enzymes like trypsin, chymotrypsin and pancreatic elastase. SLPI has also been shown to inhibit HIV-1 infections by blocking viral DNA synthesis. Since SLPI is an inhibitor of pancreatic proteases we wished to investigate whether SLPI was also actually produced in the pancreas. M-RNA from human pancreatic tissue showed evidence of SLPI production using the reverse transcriptase polymer chain reaction technique (RTPCR). Using immunohistochemical methods SLPI was demonstrated in the β-ce1ls of the islets of Langerhans. The function could be local protease/antiprotease regulation or antiviral/antibacterial defence in the close vicinity of the cell surface, or even inside the β-cell itself.